Properties and water absorption rate of paraffin wax coated paperboard - Main, Nor Mazlana; Othman, Mohd Hilmi; Marsi, Noraini; Yong, Tze Mi; Esa, Faizal; Yee, Qui Fang (Penerbit UTHM, 2020)
Paper and paperboard are the most popular packaging material nowadays. This is due to its low cost of production and biodegradable properties. Paper and paperboard are better than traditional plastics as a packaging material because of its value and sustainability. Coated paper and paperboard can be explained as a paper which is covered by a layer of plastics material or chemical which can improve the surface appearance and the mechanical properties of the paper itself...